2013
DOI: 10.1063/1.4813796
|View full text |Cite
|
Sign up to set email alerts
|

Kelvin-Helmholtz instability in non-Newtonian complex plasma

Abstract: The Kelvin-Helmholtz (KH) instability is studied in a non-Newtonian dusty plasma with an experimentally verified model [Phys. Rev. Lett. 98, 145003 (2007)] of shear flow rate dependent viscosity. The shear flow profile used here is a parabolic type bounded flow. Both the shear thinning and shear thickening properties are investigated in compressible as well as incompressible limits using a linear stability analysis. Like the stabilizing effect of compressibility on the KH instability, the non-Newtonian effect … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…3 and 4 show the plasma k 0 obtained from the ratio of heat flux and external force field (J Qz (t)/F z ) as a function of plasma coupling C, setting N¼ 500 and 4000 particles for the cases of j ¼ 3 and 4, respectively. The parts It is observed that most of the plasma k 0 data points match well with each other and reference set of data, and k 0 is usually overpredicted at the low C (1, 5) and high C (50, 100) and underpredicted at intermediate C (10,20) for N ¼ 500 (j ¼ 1). However, the plasma k 0 state points matched the reference data line for N ¼ 4000 (j ¼ 1) excellently.…”
Section: -9supporting
confidence: 63%
See 1 more Smart Citation
“…3 and 4 show the plasma k 0 obtained from the ratio of heat flux and external force field (J Qz (t)/F z ) as a function of plasma coupling C, setting N¼ 500 and 4000 particles for the cases of j ¼ 3 and 4, respectively. The parts It is observed that most of the plasma k 0 data points match well with each other and reference set of data, and k 0 is usually overpredicted at the low C (1, 5) and high C (50, 100) and underpredicted at intermediate C (10,20) for N ¼ 500 (j ¼ 1). However, the plasma k 0 state points matched the reference data line for N ¼ 4000 (j ¼ 1) excellently.…”
Section: -9supporting
confidence: 63%
“…A fluid with a linear relationship between the heat flux and the external force, giving rise to a constant thermal conductivity, may be described as a Newtonian fluid. 10 The Navier-Stokes equations are used for the description of flows of Newtonian fluid and precise solutions for Navier-Stokes equation are exceptional. For deep understanding of microscale processes, the molecular dynamics (MD) computer simulation methods have long been used and are well developed as a tool in statistical mechanics and chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…It should also be noted that, whenv 0 0y ¼ 0, there is still a viscosity dependence on the right hand side of Eq. (14). Also from Eq.…”
Section: B Non-local Analysismentioning
confidence: 94%
“…The velocity shear parameter is an important parameter for understanding the stability of such a complex system. [12][13][14] The generation of shear flow enables to measure the shear viscosity of those systems. 15 Liu et al 16 reported the dependence of shear viscosity with the temperature of dust particle, moving randomly in the system, through the Coulomb coupling parameter.…”
mentioning
confidence: 99%
“…Luo et al [37] have performed experimental studies to observe the effects of negatively charged dust particles on the K-H instability in a magnetized cesium plasma. Banerjee et al [38] have investigated the K-H instability in a non-Newtonian dusty plasma of shear flow rate dependent viscosity. Further, the role of strong coupling effects, e.g.…”
Section: Introductionmentioning
confidence: 99%